Elementary Arabic I - Issa, Sadam; Mohamed, Ayman (Open textbook library., 2022)
This open textbook is intended for beginning students of Arabic in their first semester. This OER is unique in its presentation of Arabic language content through theme-based modules. Each theme is addressed through vocabulary, grammar, reading, speaking, and writing components. Each chapter includes self-check embedded quizzes that help learners digest language concepts. The book is also designed with teachers in mind. Each chapter includes pair work and group tasks that the teacher can implement in class and other parts that can be assigned as homework. The focus of the book is to build literacy in Standard Arabic structure in a simplified and sequenced approach while emphasizing speaking skills. By the end of this course, students will be well prepared for building their competence in a sequenced and organized manner in the following parts of this series.